Pilot-scale investigation of flowrate and temperature influence on the performance of hollow fiber forward osmosis membrane in osmotic concentration process - Rem Jalab (11715205) (2020)
Forward osmosis (FO) relying on the osmotic pressure difference across semi-permeable membrane draws permeate by the effect of saline draw solution (DS) turning diluted and leaving the feed solution (FS) concentrated. However, the energy intensive step of DS recovery makes FO a challenging process. The energy benefit of FO emerges when recovery step is obviated and FO is applied as an osmotic concentration (OC) process. OC implementations for volume reduction are still at bench-scale and the investigation at larger scale is among the breakthroughs. In this paper, the performance of hollow fiber (HF) membrane in pilot-scale OC process for reducing volume of feed was investigated. The impact of operating conditions such as flowrates and temperature was evaluated. FS and DS flowrates of 1.35 and 0.35 L.min-1 respectively are optimum conditions with 75% feed recovery and 1.90 LMH water flux. Reverse solute flux increased at higher flowrates. Results indicated the role of high DS flowrate and temperature in improving the performance. DS flowrate of 0.35 L.min-1 at constant FS flow of 1.10 L.min-1 and 27 °C was most suitable for achieving 84.5% feed recovery and 1.82 LMH water flux. Above all, the long-term performance of OC pilot-plant was demonstrated through 48 h of continuous operation where stable flux trend at an average water flux of 1.66 LMH was successfully achieved. Lastly, the permeability coefficients of HF membrane were enhanced at higher temperature. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2020.104494